Pediatric Endocrinology A Practical Clinical Guide (Springer International Publishing, 2018)
A state-of-the-art and concise resource presenting the clinical management of pediatric endocrine diseases and disorders, this third edition of the highly regarded textbook covers the most common and challenging conditions seen by practicing endocrinologists and primary care physicians, including growth, hypothalamic, pituitary, adrenal, thyroid, calcium and bone, and reproductive disorders, as well as metabolic syndromes. This expanded third edition includes new topics such as conditions of overgrowth, low bone density and its management, endocrine issues related to sexual identity, mineralocorticoid disorders and endocrine hypertension, and endocrine emergencies. Some existing chapters are expanded to take into account recent advances in the field. Each chapter contains key points, an introductory discussion of the problem, a review of the clinical features that characterize it, the criteria needed to establish a diagnosis, and a comprehensive therapy section delineating the risks and benefits of the best therapeutic options available. New to this edition are concluding sections in each chapter containing relevant case material and multiple choice review questions. Pediatric Endocrinology: A Practical Clinical Guide, Third Edition is a comprehensive resource for all clinicians concerned with the myriad endocrinologic disorders seen in children and adolescents.